Biomarkers of Oxidative Stress for Neonatal Lung Disease - Ferrante, Giuliana; Carota, Giuseppe; Li Volti, Giovanni; Giuffrè, Mario (Frontiers in Pediatrics, 2021)
The transition from prenatal to postnatal life causes a significant increase in arterial oxygen tension and the activation of metabolic pathways enabling the newborn’s adaptation to the extra-uterine environment. The balance between pro-oxidant and anti-oxidant systems is critical to preserve cellular functions. Indeed, oxidative stress (OS) occurs when the production of free radicals is not balanced by the activity of intracellular antioxidant systems, contributing to cellular and tissue damage. Perinatal OS may have serious health consequences during the postnatal period and later in life. Namely, OS has been recognized as the major cause of lung injury in newborns, especially those preterm born, due to their immature lung and antioxidant systems. The development of OS biomarkers has gained increasing research interest since they may provide useful insights about pathophysiological pathways underlying OS-mediated pulmonary diseases in newborns. Moreover, their implementation in clinical settings may help to early identify high risk-newborns and to provide targeted treatment. Ideally, a biomarker should demonstrate ease of use, biological validity and reproducibility, high sensitivity and speciﬁcity. However, none of the clinically validated biomarkers so far have been qualiﬁed for neonatal lung disease. Additionally, the complex technical procedures and the high cost of such determinations have hampered the use of OS biomarkers in clinical practice. This review aims at evaluating the current evidence on the application of biomarkers of oxidative stress for neonatal lung disease and exploring the most relevant issues affecting their implementation in practice, as well as the associated evidence gaps and research limitations.